Penafsiran Kontrak Menurut Kitab Undang-Undang Hukum Perdata dan Maknanya Bagi Para Pihak yang Bersangkutan - Bambang Sutiyoso (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research purposely is to deeply figure out and understand about the estimation of contract in accordance with the civil code and the essence of the contract estimation for the concerned parties. A judicial-normative approach is applied here and the data source used in this research is simply in the form of secondary data comprising primary, secondary, and tertiary materials. Subsequently, those legal materials are analyzed using a descriptive-qualitative method. The result of the research shows that the interpretation of the contract is still needed by considering that indistinctness in the formula of contract content is often found. The interpretation of the contract is done to match the intentions of all concerned parties. To this point, there will be no any differences in fulfilling the pretasi in accordance with what has been regulated in the contract formula. In this case, both concerned parties must find the essence of a new agreement by interpreting the contract fairly. However, such interpretation is not simple as each of parties commonly has a high subjectivity that is by interpreting the contract by considering their own interest and benefit. On the other hand, the interest of other parties sometimes is not accommodated well.